Impacts of Revising Criminal Wrongful Convictions on Judicial Credibility in China: A Cocktail Party Effect Analysis - Said, Muhamad Helmi Md; Li, Yaoyao; Hassan, Muhamad Sayuti; Liu, Jingyu; Tinuk Dwi Cahyani (Universitas Negeri Semarang, 2025)
In the Disruption Era, the revision of criminal wrongful convictions is vital to the protection of human rights. Moreover, it has a wide and profound impact on judicial credibility with complex mechanisms for shaping such impact. This commitment to rectify errors and uphold justice through criminal revision, while commendable, is overshadowed by a prevailing public perception that attributes such revisions to systemic deficiencies such as corruption, misuse of authority, and biased judicial decisions. This study delves into the intricate landscape of rectifying wrongful convictions by introducing the nuanced perspective of the Cocktail Party Effect (CPE), a sophisticated acoustic theory. The CPE's impact unfolds in three distinct stages—aptly termed